INFLUENCE OF STRAIN AGEING ON CHARACTERISTICS OF DIFFERENT ARTICLES OF STEEL - E. D. Shcherbakov; V. P. Lapin; O. R. Essenson (Литьë и металлургия)
The influence of strain aging on characteristics of different steel articles is shown.